Structural and Physicochemical Interpretation of GT-STAF Information Theory-Based Indices - Barigye, Stephen J.; Marrero-Ponce, Yovani; Zupan, Jure; Pérez-Giménez, Facundo (Bulletin of the Chemical Society of Japan, 2015)
The underlying structural and physicochemical interpretation of the recently defined information indices (denominated as GT-STAF indices) is examined, with the aim of gaining greater insight on the codified chemical information. It is found that these indices are related with molecular symmetry in the context of the defined molecular “fragment” model. Moreover, these indices are sensitive to structural differences, demonstrating gradual changes consistent with modifications in the molecular structure. A principal component analysis reveals that the GT-STAF indices generally codify conformational, physicochemical, and thermodynamic properties of amino acids. A study with aniline derivatives demonstrates that the GT-STAF indices do not directly correlate with the ionization constant (pKa); but rather require multivariate contributions to yield correlations comparable with univariate models for quantum chemical parameters, suggesting that the former codify some other form of electronic information orthogonal to the latter. Finally, an evaluation of atomic contributions to the molecular hydrophobicity in furylethylenes demonstrates that the GT-STAF approach generally approximates to chemical properties quite well.
Keywords: GT-STAF; Structural; Physicochemical